2002
DOI: 10.1034/j.1601-0825.2002.20844.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary IgA and IgG subclasses in oral mucosal diseases

Abstract: Salivary immunoglobulin subclasses vary in different oral mucosal conditions and may play a role in oral mucosal inflammatory diseases and/or reflect clinical changes in these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 28 publications
9
78
0
7
Order By: Relevance
“…Sistig et al [37] did not define difference between exacerbation and remission, but they found increased salivary levels of IgA in oral lichen planus.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Sistig et al [37] did not define difference between exacerbation and remission, but they found increased salivary levels of IgA in oral lichen planus.…”
Section: Discussionmentioning
confidence: 96%
“…Altrhough Sistig [19] demonstrated an increased lervel of salivary IgA and IgG in these patients, Van der Waal [23] did not confirm that assumption.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…A IgA também tem a capacidade de neutralizar vírus presentes dentro de células epiteliais que expressam o receptor pIgR, pois quando a IgA se liga ao receptor e é transportada através da célula, ela se liga à proteína do vírus, impedindo sua replicação 19 . O signifi cado clínico sIgA ainda não está totalmente esclarecido, entretanto as avaliações de indivíduos com lesões mucosas orais, associadas aos conhecimentos teóricos e experimentos laboratoriais, sugerem que suas taxas salivares regulam o aparecimento e duração de lesões orais ou refl etem as alterações fi sopatológicas decorrentes dessas lesões 11,30 .…”
Section: Funções Da Sigaunclassified
“…O principal anti corpo presente nas mucosas e glândulas exócrinas é uma IgA polimérica, denominada IgA secretora (sIgA) [6][7][8] . Na mucosa bucal a sIgA representa a mais importante barreira imunológica, impedindo a aderência e penetração de microorganismos 4 e tem sido uti lizada como parâmetro do status imunológico dessa mucosa [9][10][11][12][13] . Devido à importância da sIgA na proteção da mucosa bucal e sua ampla uti lização na literatura como parâmetro de resposta imunológica, o presente trabalho tem como objeti vo revisar a literatura a respeito da produção, secreção e função desta imunoglobulina na proteção imunológica da mucosa bucal.…”
Section: Introductionunclassified